The Size and Growth of Firms - Singh, Ajit; Whittington, Geoffrey (Review of Economic Studies, 1975)
This paper is a sequel to the analysis of the growth process of firms presented in Chapters 4 and 5 of our book Growth, Profitability and Valuation. The relationship between size and growth of firms is explored using a more comprehensive set of data than was used in the book. In particular, the book was based on data relating to individual quoted companies in the UK in only three large industries, whereas, in this paper, we extend the analysis to cover all major industrial groups in manufacturing, construction and distribution. This paper explores the relationship between size and growth of firms, and particularly stochastic models based on the Law of Proportionate Effect or Gibrat's Law.